An Analysis of Inner Structure in Poto Watu Lo’e Traditional Ceremony in Wolokoli Village Bola Sub District Sikka Regency East Nusa Tenggara - Elisabeth Nona Marsi (Journal of English Language Teaching, Literature and Culture, 2023)
The aim of this research is to describe and identify the process and inner structure of traditional poetry Poto Watu Lo’e. The approach used in this research is the inner structure, because this approach places literary works as the basis for research and looks at literary works as a basis for research as well as a multi- layered food system as a totality that cannot be separated. The method used in this research is descriptive qualitative method namely analyzing descriptive data by describing and describing something that exited. Sources of data obtained from sources in the form of processes and traditional poetry Poto Watu Lo’e. Techniques and data collection in the form of recording, notes, observations, interviews dokumentation. Data analysis techniques buy means of translation of traditional poetry Poto Watu Lo’e, classify data, analyze data and clonclude. Based on the results of the analysis can be cloncluded as follows: the are 6 stages in the process of Poto Watu Lo’eand inner structure from Poto Watu Lo’e: first Theme (Theme of introduction and the Theme of divinity). Second Tone (Romatic Tone, Scary Tone, Reguest tone). Third Feeling (happy, Sad and embrassed). Fourth the Mandate (Mandate to maintain chastity, mandate to maintain duties and responsibilities, mandate to live always be grateful to God).